2017
DOI: 10.1002/aic.15685
|View full text |Cite
|
Sign up to set email alerts
|

Column absorption for reproducible cyclic separation in small scale ammonia synthesis

Abstract: Ammonia is rapidly and reversibly absorbed on magnesium chloride supported on alumina. The absorption at ambient temperature is twice that on alumina alone, but much of the ammonia is still captured at 400°C, closer to the temperature of ammonia synthesis. Regeneration at 450°C is complete in 30 min; partial regeneration is faster, and is correlated with the temperature and the regeneration time. The supported absorbent column works for many cycles, reproducibly, because submicron‐sized MgCl2 crystals are trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 24 publications
1
68
0
Order By: Relevance
“…It has been suggested that the condensation step of the ammonia synthesis loop could be preplaced by absorption of ammonia in crystalline salts, which can absorb ammonia at partial pressures as low as 0.002 bar at moderate temperatures. [ 50–53 ] The implementation of this over the conventional condenser for separation has the potential to allow ammonia synthesis loops to operate at pressures as low as 30 bar. [ 8 ] From the thermodynamic data shown earlier, the benefits of operating at lower temperature can be seen.…”
Section: Principles Of Catalyst Mechanismmentioning
confidence: 99%
“…It has been suggested that the condensation step of the ammonia synthesis loop could be preplaced by absorption of ammonia in crystalline salts, which can absorb ammonia at partial pressures as low as 0.002 bar at moderate temperatures. [ 50–53 ] The implementation of this over the conventional condenser for separation has the potential to allow ammonia synthesis loops to operate at pressures as low as 30 bar. [ 8 ] From the thermodynamic data shown earlier, the benefits of operating at lower temperature can be seen.…”
Section: Principles Of Catalyst Mechanismmentioning
confidence: 99%
“…The absorbent synthesis has been discussed previously, where pure salts were found to have working capacities which deteriorated with cycling. 13,27 Briefly, 30 mL of ethanol and 30 mL of methanol were added to a N 2 -purged round-bottom flask along with 6 g of anhydrous MgCl 2 (98%, Sigma-Aldrich). The solution was refluxed for 1 h under N 2 purge.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…However, significantly reducing the pressure in the Haber-Bosch process is difficult because doing so reduces reactor single pass conversion and also requires even lower temperatures for condensation of ammonia from unreacted hydrogen and nitrogen, thus increasing refrigeration demand. An alternative approach is absorbent-enhanced ammonia synthesis in which a bed of supported alkali metal salt replaces the conventional condenser [11,12]. This absorbent allows for more complete ammonia separation as compared to condensation, and subsequently, high ammonia production rates can be achieved while operating at lower pressures [13].…”
Section: Introductionmentioning
confidence: 99%